If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6 + -2x = 2x + 12 Reorder the terms: -6 + 3x + -2x = 2x + 12 Combine like terms: 3x + -2x = 1x -6 + 1x = 2x + 12 Reorder the terms: -6 + 1x = 12 + 2x Solving -6 + 1x = 12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + 1x + -2x = 12 + 2x + -2x Combine like terms: 1x + -2x = -1x -6 + -1x = 12 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + -1x = 12 + 0 -6 + -1x = 12 Add '6' to each side of the equation. -6 + 6 + -1x = 12 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 12 + 6 -1x = 12 + 6 Combine like terms: 12 + 6 = 18 -1x = 18 Divide each side by '-1'. x = -18 Simplifying x = -18
| 4x^2-36+80= | | 7x+7=17+6x | | 2/3x-15=45 | | x=105.3+3.78 | | 5x-12=73 | | 3(x+.2)=2(x-.3)+5.2 | | 14x-28=8x+3-10 | | 10a-5+7a-91=4a+20 | | (24x^6y^3)^(1/3) | | 2x-15=10x+3 | | 3x+2y=500 | | 7a-3b+15=0 | | 3a=0.026 | | 4y-7y=8y | | 36a^3/18a^4x | | -6x-15=4x+8 | | x=0.956*428.294-.347(15.27) | | 20+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6+6= | | -1+8x+46-1+8x=180 | | (-7m^2+8n^2-4n)-[(8m^2-4m+3n)+(8m^2)+4n^2]= | | 3+0.33x=5 | | x=0.956*428.294-2.39(105.3) | | 11x+2+61=180 | | -2=4x+1 | | .5x*8=1 | | 15.27=.965*x-3.78(105.3) | | 5x+10+58+5x+10=180 | | -12x+20=2x-16 | | 2y+6x=19 | | -2=4+1 | | -m-n=5 | | 2x^3-15x^2+56=0 |